Modulator power supply for 200 kV electron gun of the VEPP-5 injection complex - Akimov, A.V.; Bak, P.A.; Kazarezov, I.V.; Pachkov, A.A. (Вопросы атомной науки и техники, 2004)
The 200 kV electron gun modulator power supply based on the half-bridge converter providing the high frequency partial charge of the capacitive energy storage element is described. The algorithm developed for the power supply driving allows one to provide the soft switching of charging circuits and to achieve a high efficiency of the power supply. The data obtained at operation of the capacitive loaded 300 W power supply are presented. The prospects
of developing such type tens-kilowatts power supply are discussed. Описано пристрій високочастотного порціонного заряду ємнісного накопичувача енергії для живлення
200 кВ електронної гармати. Спеціально розроблений алгоритм керування дозволяє забезпечити м'яку
комутацію ключів зарядних контурів, домогтися високого ККД зарядного пристрою. Приведено
експериментальні дані, зняті при роботі зарядного пристрою на ємнісне навантаження потужністю 300 Вт.
Обговорюються перспективи створення зарядних пристроїв такого типу потужністю десятки кіловат. Описано устройство высокочастотного порционного заряда емкостного накопителя энергии для питания
200 кВ электронной пушки. Специально разработанный алгоритм управления позволяет обеспечить мягкую
коммутацию ключей зарядных контуров, добиться высокого КПД зарядного устройства. Приведены экспериментальные данные, снятые при работе зарядного устройства на емкостную нагрузку мощностью 300 Вт.
Обсуждаются перспективы создания зарядных устройств такого типа мощностью десятки киловатт.